DAMPAK POLA KOMUNIKASI HIPKI KAB.BANDUNG BARAT TERHADAP KINERJA LKP MEKAR SARI PADALARANG - Rizal Mochammad Fadlyansyah; Rohmalina Rohmalina (IKIP Siliwangi, 2019)
This research is motivated by the problems found in LKP Mekar Sari is the management and communicant of things that need to be observed then it can be drawn a problem in LKP Mekarsari Padalarang District West Bandung regency West Java Province problems include (1) Based on data collected by the field of program development and employment HIPKI West Java showed a decrease in activity HIPKI West Bandung regency. It is also felt by one of the institutions under the guidance of HIPKI Kab. West Bandung is LKP Mekar sari. (2) According to an inspector of West Kab.Bandung Course delivered at the event of a friendship course of West Kab.Bandung District on the occasion submitted that the lack of guidance done by HIPKI Kab.Bandung West against LKP in West Bung. (3) Despite the lack of guidance conducted by HIPKI Kab.Bandung Barat but the development of LKP in West Bandung has increased considerably as evidenced by the success of LKP MEKARSARI opened branches. (2) To know the improvement of LKP MEKARSARI performance quality after communication pattern to HIPKI (3) To know the result of HIPKI communication pattern to increase the performance of LKP MEKARSARI